Effect of Progressive Relaxation Technique on Management of State Anxiety of Judo Players: Enhancing Athletic Performance through Anxiety Management (Journal of Advances and Scholarly Researches in Allied Education, 2012)
A rapidly growing area of interest in sports psychologyconcern the use of anxiety management procedure such as bio-feedback andrelaxation training technique to enhance athletic performance by reducinganxiety. In the stressful setting provided by competitive athletics, it is notunusual to observe an athlete who either `choaked' or whose fears at leastinterfere with effective performance. Athletes who choaked or get psyched outduring athletic competition are those who cannot cope with anxiety that isalways present in sport.